Real-Time Estimation of the Output Gap in Japan and its Usefulness for Inflation Forecasting and Policymaking - Koichiro Kamada (Deutsche Bundesbank, 2004)
This paper examines the methods used by the Bank of Japan for the estimation of the output gap. Attention is paid to the real-time estimation problem. After reviewing the evolution of output gap estimation at the Bank, I discuss advantages and disadvantages of the various output gap measures. First, I examine the usefulness of the output gap for inflation forecasting and show that the real-time output gap sometimes includes much noise. Second, I investigate the implications of the real-time estimation problem for the policy evaluation. Third, I exploit TANKAN to enhance the usefulness of the real-time output gap.
Keywords: E31; E32; E52; E58; 330; output gap; real-time estimation; inflation forecasting; Taylor Rule; Kapazitätsauslastung; Schätzung; Inflation; Prognoseverfahren; Geldpolitik; Taylor-Regel; Japan